Evaluation of 2-thiothiazolidine-4-carboxylic Acid, a Common Metabolite of Isothiocyanates as a Potential Biomarker of Cruciferous Vegetable Intake (P06-017-19). (13th June 2019) - Palliyaguru, Dushani; Salvatore, Sonia; Schopfer, Francisco; Cheng, Xuemei; Zhou, Jingyang; Wendell, Stacy
Abstract: Objectives: Cruciferous vegetable consumption is associated with favorable health outcomes that are attributed to bioreactivity of isothiocyanates. These compounds exert effects that contribute to prevention of disease, in large part through attenuation of inflammation and oxidative stress. However, much about isothiocyanate metabolites and their role as biomarkers of crucifer intake remain unknown. Methods: In a clinical trial, we tested the utility and limitations of 2-thiothiazolidine-4-carboxylic acid (TTCA), an isothiocyanate-derived metabolite, as a urinary biomarker of broccoli beverage intake in a randomized crossover clinical trial where 50 participants consumed either a glucoraphanin-rich (GRR) or sulforaphane-rich (SFR) beverage. Results: Compared to run-in and wash-out periods, we observed significantly higher urinary TTCA after broccoli beverage consumption. Measurements also showed that TTCA was present in beverage powders and in all tested cruciferous vegetables. GRR resulted in excretion of ∼87% of the ingested TTCA while SFR resulted in excretion of ∼176%. Elevated urinary TTCA was also observed in rats administered 100 µmol/kg sulforaphane (SFN). Unlike SFN, TTCA did not activate nuclear factor-like 2 (Nrf2)-mediated cytoprotective signaling. Conclusions: Collectively, TTCA appears to be a common isothiocyanate-derived metabolite that has the capacity to be utilized as a biomarker of cruciferous vegetables that would be beneficial for objective and quantitative tracking of intake in studies. Funding Sources: Breast Cancer Research Foundation, NIH R35CA197222, R21AI122071, R01GM125944, R01DK112854, AHA17GRN33660955 and Chinese Medicine Science and Technology Research Foundation, Shandong Academy for Chinese Medicine 2015–317.